The formation of the Islamic understanding of kalāla in the second century AH (718- 816 CE) : between scripture and canon - Pavlovich, Pavel (Islamic History and Civilization, 2015)
In The Formation of the Islamic Understanding of kalāla in the Second Century AH (718-816 CE) , Pavel Pavlovitch studies traditions ( ḥadīth ) about the lexical and terminological meaning of the Quranic vocable kalāla . Attempts to understand kalāla began with acknowledging its unintelligibility but ultimately brought into existence a capacious body of interpretative ḥadīth , associated with early Islamic authorities. The analysis of these traditions affords insights into the changing conception of scripture during the first two Islamic centuries, the early history of Islamic exegesis and jurisprudence, and varying scholarly attitudes towards constituent sources of Islamic law. The book highlights the importance of coherent methodology of dating and reconstructing Muslim traditions according to their lines of transmission ( isnāds ) and their narrative content ( matns ).